The Loan Covenant Channel: How Bank Health Transmits to the Real Economy - CHODOROW‐REICH, GABRIEL; FALATO, ANTONIO (Journal of Finance, 2022)
ABSTRACT We document the importance of covenant violations in transmitting bank health to nonfinancial firms. Roughly one‐third of loans in our supervisory data breach a covenant during the 2008 to 2009 period, allowing lenders to force a renegotiation of loan terms or to accelerate repayment of otherwise long‐term credit. Lenders in worse health are more likely to force a reduction in the loan commitment following a violation. The reduction in credit to borrowers who violate a covenant can account for the majority of the cross‐sectional variation in credit supply during the 2008 to 2009 crisis.